2002
DOI: 10.1029/2002ja009430
|View full text |Cite
|
Sign up to set email alerts
|

NRLMSISE‐00 empirical model of the atmosphere: Statistical comparisons and scientific issues

Abstract: [1] The new NRLMSISE-00 empirical atmospheric model extends from the ground to the exobase and is a major upgrade of the MSISE-90 model in the thermosphere. The new model and the associated NRLMSIS database now include the following data: (1) total mass density from satellite accelerometers and from orbit determination (including the Jacchia and Barlier data sets), (2) temperature from incoherent scatter radar covering 1981-1997, and (3) molecular oxygen number density, [O 2 ], from solar ultraviolet occultat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

37
2,772
2
16

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 3,093 publications
(2,827 citation statements)
references
References 30 publications
(61 reference statements)
37
2,772
2
16
Order By: Relevance
“…When we ran NRL-MSIS [Picone et al, 2002;Hedin, 1983Hedin, , 1987, 1991], we found no change in Figure 7. The temperature dependence of the reaction rate β for the reaction between O + and N 2 calculated using MSIS neutral temperature and assuming that the ion temperature is the same.…”
Section: Some Simple Theoretical Aspectsmentioning
confidence: 92%
“…When we ran NRL-MSIS [Picone et al, 2002;Hedin, 1983Hedin, , 1987, 1991], we found no change in Figure 7. The temperature dependence of the reaction rate β for the reaction between O + and N 2 calculated using MSIS neutral temperature and assuming that the ion temperature is the same.…”
Section: Some Simple Theoretical Aspectsmentioning
confidence: 92%
“…These average vertical winds are plotted in Figure 10, red triangles for day 99 and blue squares for day 98, with the 1s deviation within each divergence bin displayed as an error bar for each plotting symbol. The solid black line shows the trend which would be expected from equation (5), using a scale height estimated using the NRLMSISE-00 empirical model [Picone et al, 2002], driven by geomagnetic and solar activity inputs, in addition to the all-sky average temperature measured by the Mawson SDI (for an altitude of 240 km, the assumed altitude of the airglow emission peak). Only one modeled line is shown as the scale heights for both nights were very similar, at approximately 34 km.…”
Section: Discussionmentioning
confidence: 99%
“…The simulated field line is fixed in geographic latitude and longitude, the neutral densities and temperatures are taken from the NRLMSISE-00 empirical model [Picone et al, 2002], and the vertical winds are set to zero. The magnetic field is assumed to be vertically oriented and vary with geocentric radius, r, as r −3 .…”
Section: Model Descriptionmentioning
confidence: 99%